Estimating Adult Mortality in Cameroon from Census Data on Household Deaths: 1976-1987 - Martin W. Bangha (African Population Studies, 2013)
English abstract (scroll down for abstract in French) Many African countries lack conventional data sources for systematic assessment of adult mortality. Studies of mortality in Cameroon have mainly been concerned with infant and child survival, while levels and structure of adult mortality have rarely been investigated. This paper employs the Generalized Growth Balance method to estimate adult mortality in Cameroon using data from 1976 and 1987 censuses. More specifically, we use data on household deaths during the 12 months preceding the 1976 and 1987 censuses to assess the adult mortality situation in Cameroon prior to the onset of HIV/AIDS pandemic. Results suggest that overall adult mortality in Cameroon prior to the HIV/AIDS era was high even by African standards. Ignoring potential methodological and data differences, a comparison of age-specific death rates from the two censuses to those from the recent DHS results portray a recent increase in mortality during the peak productive and reproductive years. However, a complete and reliably operational vital registration system remains the ultimate solution to estimating and fully understanding the trends in adult mortality. In the meantime, consistently collecting census data on household deaths can enhance knowledge and inform policy intervention. ------------------------------ Résumé La quasi-totalité des études sur la mortalité au Cameroun, ainsi que les efforts déployés ont été focalisé sur l'amélioration de la mortalité infantile et juvénile. Les données conventionnelles pour l'évaluation systématique de la mortalité des adultes manquent encore. Dans cet article, nous utilisons la méthode généralisée de croissance équilibrée avec les données des recensements des 1976 et 1987 pour évaluer la situation de mortalité des adultes au Cameroun. Sauf pour la mortalité infantile et juvénile, les résultats obtenus montrent que la mortalité des adultes est restée inchangée au cours de la décennie précédant l'avènement du HIV/SIDA. Une comparaison des taux de la mortalité par age pour la période considérée à ceux des résultats du EDS II et III, dépeignent une augmentation récente de la mortalité des personnes aux ages productifs et procréatifs. Les données du troisième recensement, une fois rendu publique, nous permettront éventuellement de se situer sur cette tendance.